The Decline of Queer Establishments in Hamilton, Ontario: An Exploration of Queer Space-Making - de Souza, Clare-Marie (Spectrum, 2022)
There is a lack of established 2SLGBTQ+ community spaces in Hamilton, Ontario despite its importance for community formation and identity affirmation amongst 2SLGBTQ+ people. This paper seeks to discern how many queer spaces existed from 1990-now using available digitalized archival material largely from The Hamilton Spectator newspaper. The results suggest that there is an immediate need to build 2SLGBTQ+ spaces in the city to foster deeper connections and support for queer Hamiltonians.